Integrating dual active bridge DC-DC converters: a novel energy management approach for hybrid renewable energy systems - K. Sabhi; M. Talea; H. Bahri; S. Dani (Electrical engineering & Electromechanics)
Introduction. Hybrid renewable energy systems, which integrate wind turbines, solar PV panels, and battery storage, are essential for sustainable energy solutions. However, managing the energy flow in these systems, especially under varying load demands and climatic conditions, remains a challenge. The novelty of this paper is introduces a hybrid renewable energy system structure using Dual Active Bridge (DAB) DC-DC converters and an energy management strategy (EMS) to control power flow more effectively. The approach includes a dump load mechanism to handle excess energy, offering a more efficient and flexible system operation. The purpose of this study is to develop a novel approach to managing and controlling hybrid renewable energy systems, specifically through the use of a DAB DC-DC converter. Unlike traditional methods that may struggle with efficiency and flexibility, our approach introduces an innovative EMS that leverages a reduced neural network block for real-time optimal power tracking and a sophisticated control system to adapt to dynamic conditions. This approach aims to improve the flexibility of the system, enhance energy utilization, and address the limitations of existing methods by ensuring rapid and efficient responses to changes in load and climatic conditions. The primary goal of this study is to improve the performance and reliability of hybrid renewable energy systems by optimizing energy distribution and battery management. The strategy aims to ensure continuous energy availability, enhance battery lifespan, and improve system response to dynamic changes. Methods. The proposed EMS was developed and tested using MATLAB/Simulink. The system’s control mechanism prioritizes battery charging when renewable energy output exceeds demand and redirects excess energy to a dump load when necessary. Simulations were conducted under various load and climatic conditions to assess system performance. Results. The simulation results demonstrate that the proposed strategy effectively manages energy flow, ensuring optimal power distribution, quick adaptation to load changes, and maintaining the battery’s state of charge within safe limits. Practical value. The system showed improved stability and efficiency, validating the effectiveness of the control strategy in enhancing the overall performance of hybrid renewable energy systems. References 33, tables 3, figures 13.